The call of the (Neotropical) wild: maned wolf long-range acoustic ecology - Ferreira, Luane Maria Stamatto (2019)
Maned wolves are difficult to observe in the wild because of their low densities and their cryptic and crepuscular-nocturnal habits. Exploring their long-range call – the roar-bark – is an efficient alternative for studying the species. We used a combination of methodologies: we played back roar-barks in the wolves’ natural habitat to test how free-ranging animals would respond and to understand the propagation properties of this vocalization in the wild; we recorded spontaneous roar-bark sequences of wild maned wolves using a grid of autonomous recorders for eight months to reveal long term temporal patterns; and we used captive records to access sex and individuality in the roar-bark and to test its application to natural recordings. We found that maned wolves vocalize more during the beginning of the night, and this was the only period we obtained responses during the playback experiment, despite both twilights having efficient propagation of roar-barks. Social factors may be influencing the timing of the wolves’ long-range vocal activity. We suggest that roar-barks may be an honest advertisement of quality for territorial defense. Maned wolves vocalize more on better moonlit nights, especially when the first half of the night is illuminated, likely as a consequence of reduced foraging time and therefore having more time to invest in acoustic communication. It was possible to identify the mating and circa-parturition period in our natural recordings by an increase in solo and group vocal activity, which suggests a role of roar-barks in partner attraction/guarding and intra-familiar-group communication. In captivity, male roar-barks were distinguishable by their longer duration, also indicating a sexual function and suggesting a higher energy investment to advertise motivation. Roar-barks were also individually distinct. However, site characteristics, such as presence of vegetation, drastically affected both the propagation of broadcasted roar-barks and most identity and sexual parameters’ transmission in the wild. Elevating the speaker 45° upward to simulate the head/muzzle position during vocalization lead to lower recorded sound intensities, but partially counteracted the negative effects of vegetation on signal transmission. The few stable parameters were able to discriminate individuals, although with lower success rate. In wild recordings the variation of parameters due to propagation was larger than the variation due to individual differences, therefore limiting passive acoustic monitoring as a means of counting individuals in their natural habitats. Despite the present limitation of vocal identification in the wild, bioacoustic tools proved efficient in revealing the secretive behavior ecology of maned wolves.